Nanostructured ZnO, TiO2, and Composite ZnO/TiO2 Films for Application in Dye-Sensitized Solar Cells - Myrsini Giannouli (International Journal of Photoenergy)
The effects of using composite semiconductor films on the efficiency and stability of dye-sensitized solar cells (DSSCs) were investigated. Four different types of composite ZnO/TiO2 cells were developed and sensitized with the organic molecules Coumarin 343 (C343) and Rose Bengal (RB). A comparative assessment of the different composite cells was conducted, and the photovoltaic performance of single-semiconductor ZnO and TiO2 solar cells was also compared to that of the composite ZnO/TiO2 cells. It was observed that composite cells with ZnO/TiO2 ratio equal to 90/10 have comparable efficiency to single-semiconductor cells and have the advantage of higher stability. The effects of using various multicomponent electrolytes on the efficiency and stability of the ZnO/TiO2 cells were also investigated. It was observed that the combined properties of the materials used in these electrolytes enhance the efficiency of the composite ZnO/TiO2 cells.